Lnc MSTRG 4701.7 targets miR-1786/RORa to competitively regulate proliferation and apoptosis in chicken follicular granulosa cells - Ma, Chang; Wu, Hengsong; Yan, Chunchi; Liswaniso, Simushi; Sun, Xue; Qin, Ning; Xu, Rifu (Frontiers in Veterinary Science, 2025)
BackgroundFollicular development in chickens is a highly coordinated and complex process. While the hypothalamic–pituitary-gonadal axis plays a central regulatory role in this process, the role of long noncoding RNAs (LncRNAs) remains unclear. Here, we aimed to identify key differentially expressed LncRNAs and explore their regulatory roles in follicular development, particularly focusing on the MSTRG.4701.7-miR-1786-RORa axis, to provide insights for improving fertility in low-fertility chicken varieties.MethodsIntact follicular tissues were collected from Jilin Black chickens (low-fertility group) and Lohmann Brown Laying hens (high-fertility group) at each stage of ovarian development for transcriptome sequencing to identify key differentially expressed LncRNAs for follow-up analyses. Bioinformatics analysis was also performed to determine the role of the MSTRG.4701.7-miR-1786-RORa regulatory axis, and to clarify whether that MSTRG 4701.7 targets miR-1786/RORa to competitively regulate the proliferation and differentiation of chicken follicular granulosa cells (GCs). We also knocked down and overexpressed key genes, MSTRG.4701.7 and miR-1786 and thereafter, determined changes in the mRNA and protein expression levels of axial terminal mRNA-RORa.ResultsMSTRG.4701.7 promotes the apoptosis of chicken follicular GCs, while miR-1786 reverses this phenomenon. RORa was also identified as a functional target of miR-1786 in GCs, and as a competitive endogenous RNA, MSTRG.4701.7 regulated RORa expression by sponging miR-1786, thereby playing a regulatory role in GCs. Additionally, interfering with MSTRG.4701.7 expression significantly downregulated RORa mRNA and protein expression levels, while interfering with miR-1786 showed the opposite effect.ConclusionMSTRG.4701.7 plays a critical role in follicular development in chickens by influencing GC proliferation, differentiation, and apoptosis. The resent results provide useful molecular evidence for elucidating the genetic mechanism underlying ovarian follicle development associated with egg production in chicken.